PENGARUH KOMUNIKASI KEPALA SEKOLAH DAN PENGORGANISASIAN TERHADAP MOTIVASI KERJA GURU SMPN DI KECAMATAN SANDAI - Muliansyah, Sandra; Chiar, Muhammad; Wahyudi, Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract:This study aims to find out how the description and find out how much influence the headmaster's communication and organizing have on the work motivation of teachers in the Public Middle School in the Sandai District of Ketapang Regency. This study uses a quantitative research method with a data collection tool in the form of a questionnaire. The subjects of this study were all public junior high school teachers in Sandai Subdistrict, Ketapang District, which numbered 68 people. Based on the analysis of the data, it was found that: (1) the description of the communication of principals in the Sandai District Middle School in Ketapang District was very good, with the highest number and percentage of respondents from a total of 68 respondents, 26 respondents or 38.23% with a variation of 135- 144, (2) the description of organization in the Sandai District Middle School in Ketapang District is classified as good, with the highest number and percentage of respondents from a total of 68 respondents, 27 respondents or 39.70% with variations in the number of scores 94-100, (3) organizing description in The Sandai District Middle School in Ketapang District is classified as good, with the highest number and percentage of respondents from a total of 68 respondents, 27 respondents or 39.70% with variations in the number of scores 94-100. The conclusions of this study are as follows: (1) the principal's communication has a significant effect on the motivation of working in the Public Middle School teacher in Sandai Subdistrict, Ketapang District, (2) organizing has a significant effect on the work motivation of state junior high school teachers in Sandai District, Ketapang District, Principal communication and organization together have a significant effect on the motivation of working in the State Junior High School teachers in Sandai Sub-District, Ketapang District.Keywords: Communication, Organization, Work Motivation.